2007
DOI: 10.3892/ijo.31.3.627
|View full text |Cite
|
Sign up to set email alerts
|

Induction of interleukin-8 (CXCL-8) by tumor necrosis factor-α and leukemia inhibitory factor in pancreatic carcinoma cells: Impact of CXCL-8 as an autocrine growth factor

Abstract: Abstract. Pancreatic carcinoma is one of the most lethal of the gastrointestinal malignant tumors. Chronic inflammation leads to cancer development and progression. Interleukin-8 (CXCL-8) is a CXC chemokine, which plays an important role in neutrophil chemotaxis and activation. We previously reported that CXCL-8 was produced by a variety of human carcinoma cells and tissues, and that CXCL-8 promoted proliferation in pancreatic carcinoma cells (SUIT-2). In the present study, we analyzed whether various cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 14 publications
2
39
0
3
Order By: Relevance
“…In PaCa, there are a few reports that suggest possible autocrine effects of CXCL8 in proliferation using Capan-1 and SUIT-2 pancreatic cancer cell lines. [34][35][36][37] Conversely, our previous study demonstrated that the majority of PaCa cell lines examined did not express CXCR2. 24 Moreover, in this study, we showed that ELR 1 -CXC-chemokines did not affect proliferation of commonly used PaCa cell lines including BxPC-3 and MIA PaCa-2.…”
Section: Discussionmentioning
confidence: 99%
“…In PaCa, there are a few reports that suggest possible autocrine effects of CXCL8 in proliferation using Capan-1 and SUIT-2 pancreatic cancer cell lines. [34][35][36][37] Conversely, our previous study demonstrated that the majority of PaCa cell lines examined did not express CXCR2. 24 Moreover, in this study, we showed that ELR 1 -CXC-chemokines did not affect proliferation of commonly used PaCa cell lines including BxPC-3 and MIA PaCa-2.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, only LIF-mediated STAT3 signaling has been defined in detail. Recently, dysregulation of LIF and/or the LIF receptor (LIFR) has been reported in several human malignancies, including glioblastoma (21), thyroid cancer (22), rhabdomyosarcoma (23), pancreatic carcinoma (24,25), and breast cancer (26). However, the precise role of LIF in tumorigenesis remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The first described angiogenic chemokine, CXCL8/IL-8, which binds to CXCR1 and CXCR2 [78] , is secreted by a variety of normal and tumor cells exposed to pro-inflammatory cytokines like IL-1 and TNF-α [79] . CXCR2 was associated to multiple signaling pathways involved in tumorigenesis, angiogenesis, proliferation and metastasis in several malignancies, including melanoma [80] , lung [81] , pancreatic [79,82] , gastric [83] , and ovarian [57] tumors. For instance, the overexpression of CXCR2 induced an aggressive phenotype of melanoma cells consisting with an enhanced proliferation, migration and tumor growth in mice [84] .…”
Section: Gpcrs Activated By Chemokinesmentioning
confidence: 99%